2004
DOI: 10.21273/jashs.129.2.0188
|View full text |Cite
|
Sign up to set email alerts
|

Root Growth of Avocado is More Sensitive to Salinity than Shoot Growth

Abstract: In most crop species, growth of the shoot is more sensitive to salt stress than root growth. Avocado [Persea americana Mill.] is very sensitive to NaCl stress. Even low concentrations of salt (15 mm) inhibit tree growth and decrease productivity. Observations in experimental orchards have suggested that root growth in avocado might be more restricted by salinity than shoot growth. In the present study, we evaluated quantitatively the inhibitory effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 12 publications
5
29
2
4
Order By: Relevance
“…In studies with other crops, researchers have also observed decreased shoot-root ratios with increasing salinity (Pearen et al, 1997;Bayuelo-Jiménez et al, 2003;Acosta-Motos et al, 2015). However, there are some reports of increased shoot-root ratios (Bernstein et al, 2004;AbdElgawad et al, 2016). The observation that salinity has less of an adverse effect on root growth compared with shoot growth is consistent with other observations related to stress, such as P deficiency (Fredeen et al, 1989), N deficiency (Sattelmacher et al, 1990), and drought stress (Sharp et al, 1988;Buwalda and Lenz, 1992).…”
Section: Salt Tolerancesupporting
confidence: 74%
See 1 more Smart Citation
“…In studies with other crops, researchers have also observed decreased shoot-root ratios with increasing salinity (Pearen et al, 1997;Bayuelo-Jiménez et al, 2003;Acosta-Motos et al, 2015). However, there are some reports of increased shoot-root ratios (Bernstein et al, 2004;AbdElgawad et al, 2016). The observation that salinity has less of an adverse effect on root growth compared with shoot growth is consistent with other observations related to stress, such as P deficiency (Fredeen et al, 1989), N deficiency (Sattelmacher et al, 1990), and drought stress (Sharp et al, 1988;Buwalda and Lenz, 1992).…”
Section: Salt Tolerancesupporting
confidence: 74%
“…However, shoot growth has been found to be more adversely affected by salinity than root growth (Munns and Termaat, 1986). However, there are some reports of increased shoot-root ratios (Bernstein et al, 2004;AbdElgawad et al, 2016). The root biomass per plant was reduced by 18 and 49%, respectively, while the shoot biomass was reduced by 50 and 73%, respectively.…”
Section: Salt Tolerancementioning
confidence: 97%
“…These results are in contrast to results of plants grown in saline soil (Katsuhara et al, 2003;Bernstein et al, 2004), indicating that different changing environments result in different responses of plants. Table 2 shows that changes in hydraulic traits are associated with changes in plant organ biomass and morphology in both species, which likely suggest that plant organ development gradually alters hydraulic traits.…”
Section: Different Responses Of Plants To a Changing Environmentcontrasting
confidence: 97%
“…On the other hand, hydraulic traits of roots can also affect plant organ growth and development. When a plant grows in saline soil, the hydraulic conductance of roots is very low (Katsuhara et al, 2003;Bernstein et al, 2004). This low conductance restrains the growth and development of plant organs (roots, leaves, stems) as well as that of the entire plant (Katsuhara et al, 2003;Mencuccini, 2003;Bernstein et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Shoot height and the number of survived plants decreased with the increase of salt concentrations. Decreased growth under salt stress has been reported on arocado plant species (Bernstein et al, 2004). At 12 days, the highest shoot height (19.51± 0.96) was found at 50 mM salt concentration while at 22, 32 and 42 days it was highest in control.…”
Section: Shoot Height and Live Plantsmentioning
confidence: 75%